2021
DOI: 10.1214/20-ba1218
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Multiple Changepoint Detection for Stochastic Models in Continuous Time

Abstract: A multiple changepoint model in continuous time is formulated as a continuous-time hidden Markov model, defined on a countable infinite state space. The new formulation of the multiple changepoint model allows the model complexities, i.e. the number of changepoints, to accrue unboundedly upon the arrivals of new data. Inference on the number of changepoints and their locations is based on a collapsed Gibbs sampler. We suggest a new version of forwardfiltering backward-sampling (FFBS) algorithm in continuous ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…It seems that deep seismicity was quiescent between 1955 and 1986 and active after 2007 until recently. The result is only slightly different from those in Lu (2021), as more data were collected in this analysis. We perform further analysis with conjugate prior normalΓfalse(12,6false) for λ.…”
Section: Simulation Studies and Real Data Analysiscontrasting
confidence: 85%
See 3 more Smart Citations
“…It seems that deep seismicity was quiescent between 1955 and 1986 and active after 2007 until recently. The result is only slightly different from those in Lu (2021), as more data were collected in this analysis. We perform further analysis with conjugate prior normalΓfalse(12,6false) for λ.…”
Section: Simulation Studies and Real Data Analysiscontrasting
confidence: 85%
“…We propose an efficient Gibbs sampler, which is based on an auxiliary uniformisation forward‐filtering backward‐sampling (AU‐FFBS) algorithm to sample approximately from the posterior of the number of changepoints and their positions. The method is a new application of the existing methods in Lu (2021). It is noted that both the computational and storage costs in most existing forward‐backward recursions are quadratic to n.…”
Section: Model Formulation and The Uniformisationmentioning
confidence: 99%
See 2 more Smart Citations
“…It was clearly shown that exploiting the spatial properties of the event and the structure of the sensor network can significantly reduce the ADD of the parallel multiple change-point detection compared to procedures that ignore this information. A topic for future research is multiple change-point detection in continuous time [9,15,16].…”
Section: Discussionmentioning
confidence: 99%